The Effect of Digitalization of Banks and Fintech Peer to Peer Lending on Earning with Variable Intervening Liquidity Risk - Panglipursari, Dwi Lesno; Ratnawati, Tri; Pristiana, Ulfi (International Conference On Economics Business Management And Accounting (ICOEMA), 2022)
The study aims to determine and analyze the effect of digitalization of banks and fintech Peer to Peer lending on earnings mediated by liquidity risk. The sample from this study is the monthly financial statement data of conventional commercial banks as well as the financial statements of fintech peer to peer lending in Indonesia during 2019-2021.data analysis using Smart PLS version 3.0. The results showed that bank digitalization has a significant effect on liquidity and earnings risks, but does not have a significant effect on earnings when mediated by liquidity risks. In contrast, Fintech Peer to peer lending does not have a significant effect on liquidity risk, but has a significant influence on earnings either directly or indirectly by being mediated by liquidity risk.